Disability in people with chronic low back pain treated in primary care Incapacidade em pessoas com dor lombar crônica atendidas na atenção primária - Meirelles B.H.S. (2021)
© 2021. All Rights Reserved.Introduction: Low back pain is a common musculoskeletal problem and can become chronic, with varying degrees of disability. Objective: Analyze the factors associated with disability in individuals with chronic low back pain (CLBP), treated in primary care. Methods: Cross-sectional study with 82 basic health unit (BHU) users in the municipality of Florianópolis (Brazil) with CLBP. Sociodemographic and clinical variables, health status, lifestyle and treatment were investigated. Self-rated disability was investigated using the Roland Morris questionnaire (> 14 points). The X2 or Fisher’s exact tests were used in inferential analysis for univariate association and the presence of disability. Multivariate association was analyzed by logistical regression, estimating the crude and adjusted odds ratios (OR) and their respective confidence intervals (95%CI). Results: Adults aged 40-59 years had a greater chance of developing disability (OR: 8.17; 95%: 1.21 -55.0), while professionally active individuals (OR: 0.08; 95%CI: 0.02 - 0.33) who reported engaging in physical activity > 3 times a week (OR: 0.19; IC95%: 0.04 - 0.83) had less chance of the same outcome when compared to the other participants. Conclusion: Factors related to disability were age, employment status and frequency of physical activity. Incentive strategies to return to work and engage in regular physical activity and exercise should be encouraged.